1997
DOI: 10.1002/(sici)1097-0347(199708)19:5<419::aid-hed9>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of malnutrition parameters in head and neck cancer and their relation to postoperative complications

Abstract: Abstract:Background. Malnutrition is reported frequently in head and neck cancer patients. The impact of malnutrition on surgical outcome is not clearly understood. The purpose of this study was to define the usefulness of six different parameters in scoring malnutrition and to determine the nutritional parameter primarily related to postoperative complications.Methods. Sixty-four patients undergoing major surgery for advanced head and neck cancer were studied prospectively, and six different parameters were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
106
1
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 0 publications
0
106
1
5
Order By: Relevance
“…20,21 It frequently occurs with comorbidities and with underlying disease processes, such as cancer. 22 Inadequate nutrition, particularly for cancer patients undergoing surgery, is an independent risk factor for complications, increased hospital stay and costs.…”
Section: Preoperative Nutritionmentioning
confidence: 99%
“…20,21 It frequently occurs with comorbidities and with underlying disease processes, such as cancer. 22 Inadequate nutrition, particularly for cancer patients undergoing surgery, is an independent risk factor for complications, increased hospital stay and costs.…”
Section: Preoperative Nutritionmentioning
confidence: 99%
“…Critical weight loss (CWL), defined as the involuntary weight loss of ≥5% in 1 month or ≥10% in 6 months, is a common phenomenon in head and neck cancer patients because it is present in about 30% to 55% of these patients [5,17,19,28]. CWL is clinically of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with increased morbidity and mortality. CWL may result in an increased complication rate, such as impaired wound healing, reduced immune function and decreased tolerance to surgery, radiotherapy and chemotherapy [2,25,28]. CWL also reduces disease-related quality of life and functional status [27].…”
Section: Introductionmentioning
confidence: 99%
“…4 Critical weight loss in HN cancer patients is reported to vary from 19% to 57%, depending on the timing of the weight measurements and the site of the tumor. [5][6][7][8][9] Few data are available to estimate the extent of weight loss in early stage HN cancer patients.…”
mentioning
confidence: 99%
“…10,11 In addition, patients with critical weight loss reported lower quality-of-life scores and poorer treatment tolerance. 7,[12][13][14] Several studies have shown nutritional interventions in HN cancer patients to have a positive impact on their nutritional status, quality of life, and treatment compliance. [15][16][17] In HN cancer patients, several factors contribute to weight loss before, during, and after treatment.…”
mentioning
confidence: 99%